KEPASTIAN HUKUM BAGI ISTRI DAN ANAK DALAM PERKAWINAN TIDAK TERCATAT DI INDONESIA - Moh Aqil Syofiyullah; Dyah Ochtorina Susanti; Fendy Setiawan (Fakultas Ilmu Sosial dan Humaniora, 2023)
The Marriage Registration Law in Indonesia is still not working effectively in terms of its application in society. Because some people are not too concerned with the recording itself and consider it trivial. Whereas the impact that will be caused after the occurrence of a marriage will be very large if you do not have a marriage certificate, considering that the law that is applied in Indonesia is positive law, not just Islamic law. in this study offers the concept that the government immediately revises Law No. 1 of 1974, especially regarding the mandatory registration of marriages, and given strict sanctions for the perpetrators. Because this kind of thing is very detrimental to the wife and children. So the existing regulations have not been fully able to provide legal certainty and legal protection for all levels of society in Indonesia. After analyzing the problems above, the researcher hopes that lawmakers will immediately apply strict sanctions for perpetrators of Sirri Marriage in the form of laws so as not to cause anxiety and loss to one of the parties. Because there are so many negative impacts that cause enormous harm, especially for mothers, so that the legal objectives, namely legal certainty and protection, are really well achieved.